Review of Skill Development in Higher Education in India - Pushpa Shetty, V. (AMC Indian Journal of Entrepreneurship, 2019)
With the emergence of the fourth Industrial revolution 4.0, organizations are integrating cutting-edge technologies into their operations to face the challenges of evolving IT trends. Meanwhile, the organizations are also upgrading technological infrastructure. Workforce is struggling to keep pace with the fast changing and evolving technical skill sets. While it is alarming to note the pace at which digital revolution is taking the world by quantum leaps, regrettably the rate of digital adoption is negligible. Many eminent industrialists including Infosys co-founder N. R. Narayan Murthy have voiced concerns of a talent crunch in the county impacting youth, and in turn entrepreneurship. With this backdrop, the need for skilling is gaining importance. This need has accelerated for policy-backed skill development initiatives of government of India to realize the potential of the youth for employability and entrepreneurship. However, there exists a huge gap between the current status and the desired goals in terms of skill development. With the advantage of ’demographic dividend’ which is a pride and source of strength of India, the graduating students were the centre of focus of this study. This study is a conceptual study exploring the need for imparting skills to the youth to bridge the gap of skill requirement in the industry for employment or entrepreneurship, and the initiatives taken by government of India for higher education. This paper will be of interest to students, academicians, and industry professionals.